(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This study examines the relationship between banking sector development and economic growth in Punjab. A well-developed banking sector plays a crucial role in mobilizing savings, facilitating investments, promoting financial inclusion and supporting industrial and agricultural activities. Punjab, being an agrarian and industrially significant state, depends heavily on an efficient financial system for sustainable economic development. The research analyzes key indicators of banking sector development such as credit growth, branch expansion, deposit mobilization and financial outreach and evaluates their impact on the state’s economic performance. Using secondary data collected from RBI reports, state economic surveys and government publications, the study employs quantitative techniques to identify trends and correlations between banking development and economic growth. The findings reveal that expansion of banking services has positively contributed to capital formation, employment generation and income growth in Punjab. The study highlights the need for policy initiatives to strengthen rural banking, digital finance and credit accessibility to enhance inclusive growth. The research concludes that a robust banking system is a key driver of sustainable economic development in Punjab.